Causes and consequences of crisis on the market for secondary raw materials. - Gojišová, Ivana (2010)
Subject matter of the diploma thesis is a crisis on the market for secondary raw materials. The crisis was observed in the end of 2008 and in beginning of 2009. The diploma thesis is deal with current situation on the market for recycling and identifying its specifics. First, it is focused on the European Packaging Waste Directive institutional framework of the market for recycling. Consequently it is discussed how successful is implemented Directive in each European Union member country. The second chapter is about the market for recycling and about the recent crisis. In the third chapter we discover causes and consequences in connection with the collapse and we will confront with specialists through the interviews. In the last part of the diploma thesis is suggested original solution.